Optimized approach to conduct hydraulic fracturing test on true tri-axial stress condition - Feng, R.; Wang, H.; Abdolghafurian, M.; Tarom, N.; Hossein, S.; Ezdini, A.; Rezagholilou, Ali (2018)
Copyright © 2018 ARMA, American Rock Mechanics Association. Hydraulic fracturing has been widely applied to enhance hydrocarbon recovery in oil and gas field, especially for unconventional reservoir in which the permeability is usually nano-Darcy. In the field implementation, numerical modelling is initially performed, then the field testing (i.e. minifrac test) are conducted to infer the geological parameters. However, it is vital to perform laboratory tests (i.e. rock mechanical and hydraulic fracturing tests.) to obtain the rock mechanical parameters and important observations, which helps to mitigate uncertainties and risks encountered in both simulation modelling and field testing. Thus, a series of rock mechanical tests (i.e. unconfined/confined compressive, Brazilian tensile, and semi-circular bending) were conducted. Scaling analysis and true triaxial stress cell were applied to ensure the fracture propagated at the analogues field condition. Next, the logistic experimental procedure was explained and hydraulic fracturing tests were conducted on the 10cm cubic samples under true triaxial stresses. The unpredictable results were discussed and the optimized approaches were proposed. We concluded that system leakage and unbalanced stress loading can be detected and fixed at the earlier stage to avoid the sample was damaged.